Evaluasi Sistem Informasi Sumber Daya Manusia Pada PT XYZ - I Gusti Made Karmawan; Tangkas Udiono; Abdul Haris (Bina Nusantara University, 2010)
The research objective was to evaluate the procedures and internal controls of Human Resource Information System XYZ. To that end, the author conducted the examination, collecting, previews and documenting the evidence that supports the information systems, so that it can find problems that occur in information systems and measure risk on internal controls to produce recommendations that can be considered. To support the research, the research uses a library, where the data obtained by reading a book and browse the website in accordance with the research are discussed. And with a field research method, which was obtained through a check list, interview and observation. Results of evaluation on the current information system, gives the conclusion that the current system has been implemented according to the company the current procedure, but found few risks to the internal controls within them.